Management System Adoption: Its Effect on Employee Satisfaction and Productivity in a Local Drugstore in the Philippines - Czedrick Faller; Khyla Marie M Gamil; Joel B Casungcad; Mary Rhanessa Edar; Franz Aries N Ilao; Jesus P Briones; Joanna Paula E Verano (People and Behavior Analysis, 2025)
The effective implementation of a relevant structured management system is considered beneficial to organizations across various industry sectors, promotingpositive institutional and employee outcomes. This study examined the impact of implementing a management system on employee satisfaction and productivity in a local drugstore in the Philippines. Data were gathered from 197 employees using a researcher-structured questionnaire. They employed a descriptive-correlational quantitative research design with frequency and percentage distribution, weighted mean, and t-test as tools used in data analysis. Findings showed that prior to adopting the management system, employee satisfaction with job content and clarity, role clarity, and compensation and benefits were considered acceptable; however, employees expressed dissatisfaction with their career growth and development. After implementation, satisfaction levels increased significantly increased across all dimensions. Productivity also improved, particularly in quality of work, teamwork, and feedback mechanisms, although time management and absenteeism still presented minor areas for improvement. Statistical analysis confirmed significant gains in satisfaction across all dimensions following adoption. From a managerial perspective, the study underscored the importance of structured management systems in fostering organizational effectiveness. Theoretically, it contributed to the discourse on the importance of structured frameworks in the Philippine business setting. However, the single-industry focus limits the generalizability of the findings, and future research should consider diverse sectors and longitudinal designs to assess long-term effects.